2018
DOI: 10.1155/2018/5109497
|View full text |Cite
|
Sign up to set email alerts
|

miR-144-5p Enhances the Radiosensitivity of Non-Small-Cell Lung Cancer Cells via Targeting ATF2

Abstract: MicroRNAs (miRNAs or miRs) regulate gene expression at the posttranscriptional level and are involved in many biological processes such as cell proliferation and migration, stem cell differentiation, inflammation, and apoptosis. In particular, miR-144-3p is downregulated in various cancers, and its overexpression inhibits the proliferation and metastasis of cancer cells. However, the role of miR-144-5p in non-small-cell lung cancer (NSCLC), especially radiosensitivity, is unknown. In this study, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 37 publications
2
44
0
2
Order By: Relevance
“…It has been reported that miR‐124 can enhance the radiation‐induced apoptosis of NSCLC cells via inhibition of STAT3 . Similarly, miR‐144‐5p can enhance the radiosensitivity of NSCLC cells by regulating ATF2 . In our present study, radiation therapy can increase the expression of miR‐155‐5p and miR‐760 in NSCLC cells.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…It has been reported that miR‐124 can enhance the radiation‐induced apoptosis of NSCLC cells via inhibition of STAT3 . Similarly, miR‐144‐5p can enhance the radiosensitivity of NSCLC cells by regulating ATF2 . In our present study, radiation therapy can increase the expression of miR‐155‐5p and miR‐760 in NSCLC cells.…”
Section: Introductionsupporting
confidence: 48%
“…We firstly investigated the roles of radiation on migration and invasion of NSCLC cells. It has been reported that radiation greater than 5 Gy can significantly inhibit the proliferation of NSCLC cells . Our data showed that the radiation of 2 Gy, which had no significant effect on cell proliferation , can significantly inhibit the wound healing of A549 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-144 is detected in lung cancer cells with the expression of upregulated glucose transporter 1 (GLUT1) and enhanced glucose uptake [139]. Moreover, miR144-5p increases the radiosensitivity in NSCLC cells by targeting activating transcription factor 2 (ATF2) [140]. Chen Y et al evaluated the downregulation of miR-144-3p and its clinical value in NSCLC.…”
Section: Mir-144 In Lung Cancermentioning
confidence: 99%
“…4,5 Among those biomarkers, some act as protooncogenes, and some are considered as antioncogenes via controlling the survival and metastatic capacities of tumor cells. It has been well-established that miRNAs contribute to a wide range of physiological and pathological events, including the occurrence and development of various tumors.…”
Section: Introductionmentioning
confidence: 99%